2020
DOI: 10.7570/jomes20030
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Patients’ Regular Participation at an Obesity Center to Evaluate the Effects on Mental Status and Blood Parameters

Abstract: Background: Obesity is the main cause of type 2 diabetes, coronary artery disease, musculoskeletal disorders, some cancers, and mental disorders, and many other diseases leading to mortality. The aim of this study was to determine the effects of participation in an obesity center on patient mental status and blood parameters within 3 months and to show the relationship of this participation with depression, anxiety, and other parameters. Methods: This was a descriptive and cross-sectional study. Of 2,591 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a study conducted at an obesity center in Konya, the BMI values of the patients, who regularly attended the trainings at the center, were reported to have decreased in the 3 rd month controls from 39.45 ± 5.90 to 36.85 ± 5.68, waist circumference from 110.10 ± 11.30 cm to 102.83 ± 10.66 cm, and the hip circumference from 128.94 ± 11.60 cm to 122.29 ± 11.05 cm (12).We found out that the participants, who all met the requirement of regular participation in our trainings mentioned in the Yıldırım's study, had an average of 161.1 ± 82.97 days of daily follow-up, during which the BMI fell from 36.9 (30-65.2) kg/m 2 to 32.6 (24.68-58.9) kg/m 2 , waist circumference from 111 (85-189) cm to 100 (74-166) cm, and the hip circumference from 118 (97-182) cm to 108 (86-176) cm. The same study also examined the changes in blood parameters in line with the weight loss in the 3 rd month and revealed that there was a significant decrease in HbA1c, LDL-C and triglyceride levels, and a minimal decrease in HDL-C level, although not significant 12 . Our results came to a similar conclusion with that of Yıldırım.…”
Section: Discussionmentioning
confidence: 96%
“…In a study conducted at an obesity center in Konya, the BMI values of the patients, who regularly attended the trainings at the center, were reported to have decreased in the 3 rd month controls from 39.45 ± 5.90 to 36.85 ± 5.68, waist circumference from 110.10 ± 11.30 cm to 102.83 ± 10.66 cm, and the hip circumference from 128.94 ± 11.60 cm to 122.29 ± 11.05 cm (12).We found out that the participants, who all met the requirement of regular participation in our trainings mentioned in the Yıldırım's study, had an average of 161.1 ± 82.97 days of daily follow-up, during which the BMI fell from 36.9 (30-65.2) kg/m 2 to 32.6 (24.68-58.9) kg/m 2 , waist circumference from 111 (85-189) cm to 100 (74-166) cm, and the hip circumference from 118 (97-182) cm to 108 (86-176) cm. The same study also examined the changes in blood parameters in line with the weight loss in the 3 rd month and revealed that there was a significant decrease in HbA1c, LDL-C and triglyceride levels, and a minimal decrease in HDL-C level, although not significant 12 . Our results came to a similar conclusion with that of Yıldırım.…”
Section: Discussionmentioning
confidence: 96%